Anthropometric predictors of basal metabolic rate in professional athletes - Severi, S.; Bedogni, G.; Battistini, N.; Tripi, F. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Basal metabolic rate (BMR) is commonly estimated from body weight (Wt) and height (Ht) because these anthropometric dimensions explain a great portion of fat-free mass (FFM) variability in sedentary or moderately active subjects. However, changes in FFM composition occur in professional athletes that may render this approach less accurate than in sedentary or moderately active subjects. We studied the relationship between BMR estimated from O2 consumption and CO2 production (SensorMedics Vmax) and selected anthropometric dimensions in 30 male subjects practicing basketball or volleyball at professional level. Wt explained 48% of BMR variance (p < 0.001) and residuals of this regression (BMR:Wt) were significantly correlated with age (adj R2 = 0.28), triceps skinfold (TSF; adj r2 = 0.27) and biceps skinfold (BSF; R2 = 0.28) (p < 0.005 for all R2 values). However, BMR:Wt was uncorrelated with Ht, body mass index, subscapular skinfold, suprailiac skinfold, arm circumference, waist circumference and hip circumference. TSF and BSF were highly correlated (r = 0.71, p < 0.0001) but none of them was associated to age (p = ns). A predictive model based on Wt, TSF and age explained 78% of BMR variance with a SEE of 150 Kcal x day -1 (7.3%). Although it cannot be excluded that the special features of our subjects (whose Ht was comprised between 173 and 202 cm and whose age varied between 18 and 31 y) may have influenced the contribution of Ht and age in predicting BMR, the fact that arm skinfolds explained about 28% of BMR:Wt variance suggests that anthropometric parameters other than Wt and Ht may be useful to estimate BMR in professional athletes.